Beyond Conventional Boundaries: A Literature Study on Madrasah Management and the Construction of Online Learning Innovations - Muhammad Anggung Manumanoso Prasetyo; Bashori Bashori; Novi Nur Lailisna (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
In the current era of the new normal, substantial transformations are unfolding within the education sector. E-learning has emerged as a prevalent alternative for augmenting individual proficiencies and abilities. Madrasahs have transcended the confines of scientific dichotomy, instead embracing innovation and change. The online learning process, when effectively implemented, significantly impacts student quality improvement. This research aims to comprehensively analyze the dynamics of online learning, thereby discovering an online learning model in madrasas. The study is qualitative, using library analysis techniques. Data sources are derived from the results of scientific journal research or primary books. The study results identify various online learning modalities, namely (1) the contribution and significance of leadership roles in policy and building a culture that supports the learning process; (2) the enhancement of teacher and manager professionalism, specifically emphasizing technical skills (cognitive-practical); (3) the implementation of continuous monitoring and evaluation of the program's success, as well as a means of feedback on the direction of online learning. The research results also reveal that resource availability, teacher readiness, self-confidence, student accessibility, and motivation play essential roles in learning integrated with information technology.